Urgensi dan Tata Kelola Super Holding BUMN: Studi Komparatif Danantara Indonesia, Temasek Holdings Singapura, dan 1MDB Malaysia - Nidia Yustisia Kartika; Muhammad Bilal Prasetyo; Mustofa Ponco Wibowo (CV Rewang Rencang, 2025)
This study aims to compare the governance between Danantara, Temasek, and 1MDB. The focus on the study includes legal basis, ownership status, organizational structure, and accountability system. Danantara has a strong legal basis but remains vulnerable to political influence and weak oversight. Temasek has maintained its independence through a strong legal and organizational structure, while 1MDB exemplifies governance failure due to weak oversight and lack of transparency. This study highlights the need for transparency, accountability, and political neutrality to ensure the success of state-owned superholdings and offers insights for developing a sustainable state investment model.